2007
DOI: 10.1111/j.1365-2958.2007.06069.x
|View full text |Cite
|
Sign up to set email alerts
|

DivS, a novel SOS‐inducible cell‐division suppressor in Corynebacterium glutamicum

Abstract: SummaryDNA damage-induced SOS response elicits the induction of cell-division suppressor as well as DNA repair genes. In Gram-positive bacteria, cell-division suppressor genes, so far characterized from Bacillus subtilis (yneA) and Mycobacterium tuberculosis (rv2719c), share limited homology, but are both located in the vicinity of lexA on their respective genomes. Using this proximity to lexA, Corynebacterium glutamicum R divS (cgR1759) was identified as an SOS-inducible cell-division suppressor in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 46 publications
3
61
1
Order By: Relevance
“…For several bacteria the products of a number of SOS-response genes have been found to inhibit this process. Such genes include sulA for E. coli (Huisman et al, 1984), yneA for B. subtilis (Kawai et al, 2003), Rv2719c for Mycobacterium tuberculosis (Chauhan et al, 2006), and divS for Corynebacterium glutamicum (Ogino et al, 2008). These studies reported the occurrence of cell elongation as a consequence of the SOS response.…”
Section: Discussionmentioning
confidence: 85%
“…For several bacteria the products of a number of SOS-response genes have been found to inhibit this process. Such genes include sulA for E. coli (Huisman et al, 1984), yneA for B. subtilis (Kawai et al, 2003), Rv2719c for Mycobacterium tuberculosis (Chauhan et al, 2006), and divS for Corynebacterium glutamicum (Ogino et al, 2008). These studies reported the occurrence of cell elongation as a consequence of the SOS response.…”
Section: Discussionmentioning
confidence: 85%
“…The lexA gene (cg2114) of C. glutamicum ATCC 13032 is located in a head-to-head arrangement with the divS-nrdR (cg2113-cg2112) transcription unit (Fig. 1a), encoding a cell division suppressor and a regulator of deoxyribonucleotide biosynthesis (Borovok et al, 2004;Ogino et al, 2008;Rodionov & Gelfand, 2005). Downstream of the nrdR gene, a coding region for a putative ATP-dependent helicase has been predicted ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining genes encode hypothetical proteins with unknown functions, including secreted proteins, putative membrane proteins and potential transporters (Tables 2, 3 and 4). The only regulatory genes directly controlled by the LexA protein are lexA itself and the divergently oriented divS and nrdR genes, encoding a regulator of cell division and a DNA binding transcription regulator of ribonucleotide reductase, respectively (Borovok et al, 2004;Ogino et al, 2008;Rodionov & Gelfand, 2005). Interestingly, the three regulatory genes are located in a highly conserved gene region of the hitherto sequenced corynebacterial genomes (Fig.…”
Section: Verification Of Differential Gene Expression By Rt-pcr and Dmentioning
confidence: 99%
See 1 more Smart Citation
“…A DNA fragment containing the promoter region of the bglF2 gene of C. glutamicum strain R was amplified by PCR using the primer pair PbglF2-F and PbglF2-R (supplemental Table S1) and was cloned between the EcoRI and SacI sites of a shuttle vector, pCRC500 (20), to construct pCRC531. DNA fragments containing the qorR coding region were excised from pCRD610 and pCRD611 (see below) with NdeI and HindIII and cloned between the NdeI and HindIII sites of pCRC531 to construct pCRD630 and pCRD631, respectively.…”
mentioning
confidence: 99%